Recurrent thrombosis in a multiple myeloma patient with low risk for thrombosis despite being on thromboprophylaxis - Chow Siew Kian; Fu Mei Sian (Archives of Hematology Case Reports and Reviews - Peertechz Publications, 2019)
It is a well-known fact that multiple myeloma (MM) patients have an increased risk for thromboembolic events involving both the venous and arterial territories. The etiologies can be multifactorial, for example, activation of procoagulant factors, acquired protein C resistance, MM-specified and treatment-related factors. The risk of venous thrombosis is high when patients receive treatment with thalidomide or lenalidomide in combination with dexamethasone or multi-agent chemotherapy. Arterial thromboses occur less compared to venous thrombotic events. Nonetheless, thromboprophylaxis is important in preventing both types of thromboses. In this case study, we reveal a patient whom thrombosis occurred concurrently in both arterial and venous despite being on aspirin prophylaxis.